A review of high ideality factor in gallium nitride-based light-emitting diode - Hedzir, A.S.; Hasbullah, N.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Theory concerning the high ideality factor of gallium nitride (GaN) based light-emitting diode (LED) has been reviewed. The presence of a high ideality factor indicates a large forward voltage that results in efficiency reduction. The paper suggests that tunneling is the main reason defining the exponential behaviour of current-voltage measurements, which leads to a high ideality factor. However, there is also a paper that suggests that the design of the current geometry in the LED chip defines the value of the ideality factor. An effective current spreading geometry in the LED chip will minimize the ideality factor and make it fall between the ideal range of 1 to 2. Besides, how the ideality factor is calculated will also play a major role in defining its value. By calculating the ideality factor based solely on the radiative recombination current formula, the value of the ideality factor can result in an ideal ideality factor of 1.08. Розглянуто теорію великих значень коефіцієнта ідеальності у світлодіоді на основі нітриду галію. Наявність великого коефіцієнта ідеальності свідчить про велику пряму напругу, що призводить до зниження ефективності. У статті висловлено думку, що тунелювання є основною причиною, яка визначає експоненційну поведінку вольт-амперних характеристик, що призводить до великих значень коефіцієнта ідеальності. Однак є також стаття, яка передбачає, що дизайн геометрії струму світлодіодного чіпа визначає величину коефіцієнта ідеальності. Ефективна геометрія розподілу струму в світлодіодному чіпі дозволить мінімізувати коефіцієнт ідеальності та змусить його набувати значень в ідеальному діапазоні від 1 до 2. Крім того, спосіб розрахунку коефіцієнта ідеальності також відіграє важливу роль у визначенні його величини. Якщо обчислювати цей коефіцієнт, виходячи виключно з формули для струму випромінювальної рекомбінації, то величина коефіцієнта ідеальності може досягати ідеального значення 1,08.